2021
DOI: 10.5546/aap.2021.eng.e298
|View full text |Cite
|
Sign up to set email alerts
|

Respect for individual autonomy and a collective benefit: Arguments in favor of compulsory SARS-CoV-2 vaccination among health care professionals

Abstract: With the development of SARS-CoV-2 vaccines, a new aspect to be taken into consideration in the midst of the pandemic is vaccine refusal. Since vaccination is voluntary, it is necessary to deal with the fact that some health care team members refuse to receive it. Here I put forward different bioethical arguments: Kantian deontology and the principles of universalizability, humanity, and autonomy; Mill's utilitarianism, with selfprotection as the sole end for which humankind is authorized to interfere with its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Some authors suggested complicating the procedure for refusing the vaccine to support this approach [ 76 ]. In addition, the violation of autonomy can be justified by arguing that the public interest (public health) “is the intimate and ultimate determining factor of individual freedom and is above any individual benefit” [ 77 ]. However, these approaches cannot be easily justified through an ethical lens.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggested complicating the procedure for refusing the vaccine to support this approach [ 76 ]. In addition, the violation of autonomy can be justified by arguing that the public interest (public health) “is the intimate and ultimate determining factor of individual freedom and is above any individual benefit” [ 77 ]. However, these approaches cannot be easily justified through an ethical lens.…”
Section: Discussionmentioning
confidence: 99%